Mesenchymal Stromal Cell-Derived Extracellular Vesicles Modulate Hematopoietic Stem and Progenitor Cell Viability and the Expression of Cell Cycle Regulators in an Age-dependent Manner - Fichtel, Pascal; von Bonin, Malte; Kuhnert, Robert; Möbus, Kristin; Bornhäuser, Martin; Wobus, Manja (Frontiers in Bioengineering and Biotechnology, 2022)
Aging of the hematopoietic system is characterized by an expansion of hematopoietic stem and progenitor cells (HSPCs) with reduced capacity for engraftment, self-renewal, and lymphoid differentiation, resulting in myeloid-biased hematopoiesis. This process is mediated by both HSPC intrinsic and extrinsic factors, e.g. the stromal environment. A relevant cellular component of the bone marrow (BM) microenvironment are mesenchymal stromal cells (MSCs) which regulate fate and differentiation of HSPCs. The bi-directional communication with HSPCs is mediated either by direct cell-cell contacts or by extracellular vesicles (EVs) which carry bioactive substances such as small RNA, DNA, lipids and proteins. So far, the impact of MSC-derived EVs on human hematopoietic aging is poorly investigated. BM MSCs were isolated from young (n=3, median age: 22 years) and aged (n=3, median age: 70 years) donors and the EVs were isolated after culturing the confluent cell layer in serum-free medium for 48 hours. CD34+ HSPCs were purified from peripheral blood of healthy donors (n=3, median age: 65 years) by magnetic sorting. Nanoparticel tracking analysis (NTA), transmission electron microscopy (TEM) and western blot detection of EV markers CD63, CD81 and Flotillin-1 revealed no significant differences between young and aged MSC-EVs. Interestingly, young MSCs secreted a significantly higher miRNA concentration than aged cells. However, the amount of distinct miRNAs such as miR-29a and miR-34a was significantly higher in aged MSC-EVs. HSPCs incubated with young EVs showed a significant increase in cell number and a higher viability. The expression of the tumor suppressors PTEN, a known target of mir-29a, and CDKN2A was increased in HSPCs incubated with young EVs. The clonogenic assay demonstrated a decreased colony number of CFU-GM after treatment with young EVs and an increased number of BFU-E/ CFU-E after incubation with aged MSC-EVs. Xenogenic transplantation experiments showed no significant differences concerning the engraftment of lymphoid or myeloid cell compartments, but the overall human chimerism 8-16 weeks after transplantation was higher after EV treatment. In conclusion, our data suggest that HSPC characteristics such as cell cycle activity and clonogenicity can be modulated by MSC-derived EVs. Further studies have to elucidate the potential therapeutic relevance of our findings.